Ubiquitination contributes to the regulation of GDP-mannose pyrophosphorylase B activity - Franzka, Patricia; Mittag, Sonnhild; Chakraborty, Abhijnan; Huber, Otmar; Hübner, Christian A. (Frontiers in Molecular Neuroscience, 2024)
GDP-mannose pyrophosphorylase B (GMPPB) loss-of-function is associated with muscular dystrophy and variable additional neurological symptoms. GMPPB facilitates the catalytic conversion of mannose-1-phosphate and GTP to GDP-mannose, which serves as a mannose donor for glycosylation. The activity of GMPPB is regulated by its non-catalytic paralogue GMPPA, which can bind GDP-mannose and interact with GMPPB, thereby acting as an allosteric feedback inhibitor of GMPPB. Using pulldown, immunoprecipitation, turnover experiments as well as immunolabeling and enzyme activity assays, we provide first direct evidence that GMPPB activity is regulated by ubiquitination. We further show that the E3 ubiquitin ligase TRIM67 interacts with GMPPB and that knockdown of TRM67 reduces ubiquitination of GMPPB, thus reflecting a candidate E3 ligase for the ubiquitination of GMPPB. While the inhibition of GMPPB ubiquitination decreases its enzymatic activity, its ubiquitination neither affects its interaction with GMPPA nor its turnover. Taken together, we show that the ubiquitination of GMPPB represents another level of regulation of GDP-mannose supply.